Ice friction: the effect of thermal conductivity - Kietzig, A.-M.; Hatzikiriakos, S. G.; Englezos, P. (Journal of Glaciology, 2010)
The effect of thermal conductivity on ice friction is studied systematically for different metallic slider materials over a wide range of temperatures, and sliding velocities. By thermally insulating the slider with fiberglass, the isolated effect of thermal conductivity on ice friction is investigated. A decrease of the friction coefficient in the boundary friction regime and an earlier onset of the mixed friction regime in terms of sliding velocity are found. Furthermore, the dependence of the ice friction coefficient on sliding velocity is compared for different sliding materials. It is found that the influence and importance of thermal conductivity decreases with increasing sliding velocity.